Evaluating trespass prevention: working with young people as co-researchers and filmmakers on a railway safety project - Ryan Josiah Bramley; Marion Oveson; Aneesh Barai (International Journal of Adolescence and Youth, 2024)
Recent attempts have been made by Network Rail and the British Transport Police to discourage young people from committing ‘railway trespass’ – the dangerous act of illegally gaining access to live railway tracks. Whilst public safety campaigns have a long history in the UK and beyond, little research has been dedicated to a better understanding of how young people engage with this media. This article reflects on Evaluating Trespass Prevention (2021), a project which involved a small group of Further Education (FE) Media Students as co-researchers exploring railway trespass prevention. The young co-researchers co-produced a new evaluation toolkit, as well as creatively exploring themes of railway trespass through documentary interviewing and filmmaking. Presenting our critical reflections on the process of working with young co-researchers on this project, we argue for the broader adoption of an adaptable and iterative approach to meaningful engagement with young people in relation to contemporary social issues.